Work Readiness of New Graduate Physical Therapists for Private Practice in Australia: Academic Faculty, Employer, and Graduate Perspectives. Issue 6 (3rd March 2021) - Wells, Cherie; Olson, Rebecca; Bialocerkowski, Andrea; Carroll, Sara; Chipchase, Lucy; Reubenson, Alan; Scarvell, Jennie Mary; Kent, Fiona
Abstract: Objective: The purpose of this study is to explore academic faculty, employer, and recent graduate perspectives of the work readiness of Australian new graduate physical therapists for private practice and factors that influence new graduate preparation and transition to private practice. Methods: This study used a mixed-methods design with 3 surveys and 12 focus groups. A total of 112 participants completed a survey, and 52 participated in focus groups. Descriptive statistics were used to summarize the quantitative data, and thematic analysis was used to analyze the qualitative data. Triangulation across participant groups and data sources was undertaken. Results: Australian new graduate physical therapists were perceived to be "somewhat ready" for private practice and "ready" by their third year of employment. Participants proposed that new graduates bring enthusiasm, readiness to learn, and contemporary, research-informed knowledge. New graduates were also perceived to find autonomous clinical reasoning and timely caseload management difficult; to have limited business, marketing, and administration knowledge and skills; and to present with underdeveloped confidence, communication, and interpersonal skills. Factors perceived to influence graduate transition included private practice experience, such as clinical placements and employment; employer and client expectations of graduate capabilities; workplace support; university academic preparation and continuing education; and individual graduate attributes and skills. Conclusion: Australian new graduate physical therapists have strengths and limitations in relation to clinical, business, and employability knowledge and skills. New graduate work readiness and transition may be enhanced by additional private practice experience, employer and client expectation management, provision of workplace support, and tailored university and continuing education. Impact: The number of new graduate physical therapists employed in private practice in Australia is increasing; however, until this study, their work readiness for this setting was unknown. This exploration of new graduate performance in private practice and transition can help to increase understanding and enhancement of work-readiness.